Faktor-Faktor yang Berhubungan dengan Keberhasilan Pemberian ASI Eksklusif - Lina Herlina; Nirmala Harahap; Sobar (Politeknik Karya Husada, 2025)
Exclusive breastfeeding is one of the most important efforts in improving infant and maternal health, but its implementation still faces various challenges that are influenced by a number of factors. Support from health workers, the role of husbands, and exposure to formula milk promotions are aspects that potentially affect the success of exclusive breastfeeding, especially at the local community level. This study aims to identify the factors that influence the success of exclusive breastfeeding among breastfeeding mothers in TPMB Susi Primayanti, A.Md. Keb Pandak Village, Baturaden District, Banyumas Regency, Central Java. The method used was descriptive analytic design with a cross-sectional approach, involving 82 respondents selected through purposive sampling technique. Data were collected through questionnaires that included variables of health worker support, husband support, exposure to formula milk promotion, age, and mother's education. Univariate analysis showed that 47.6% of respondents exclusively breastfed, while 52.4% did not. Bivariate analysis showed a significant relationship between health worker support (p = 0.00), husband support (p = 0.00), exposure to formula milk promotion (p = 0.04), age (p = 0.002), and maternal education (p = 0.004) to the success of exclusive breastfeeding. This study concluded that support from health workers and husbands plays an important role in increasing the success of exclusive breastfeeding. The findings are expected to be a reference for health workers and government policies in improving the exclusive breastfeeding program in Indonesia.